Transformasi Literasi Digital Sebagai Sarana Pembentukan Kesadaran Kewarganegaraan di Era Ruang Publik Virtual - Kornelia Efriana Mumung; Denti Sulistiawati (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The development of digital technology has transformed the way citizens interact, learn, and participate in virtual public spaces. This transformation presents opportunities for strengthening civic values, but also poses challenges in the form of a moral crisis and low media ethics among the younger generation. This study aims to analyze how digital literacy plays a role in fostering civic awareness and how Civic Education (PPKn) education can transform in the digital era. This study used a literature review method by reviewing various scientific sources such as journals, books, and relevant research reports. The results indicate that digital literacy plays a strategic role in developing critical thinking skills, social empathy, and ethical responsibility in cyberspace. The transformation of PPKn education needs to be directed at strengthening teachers' digital competencies, innovating collaborative learning methods, and strengthening educational policies that support the integration of technology and Pancasila values. Thus, digital literacy is not merely a technical skill, but also a moral and social tool for developing intelligent, reflective, and nationally characterized digital citizens.